2020
DOI: 10.1155/2020/1747894
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cell Profile and Activation Response in Sickle Cell Disease Patients with Osteonecrosis

Abstract: Recent evidence suggests that abnormalities involving CD4+T lymphocytes are associated with the pathophysiology of osteonecrosis (ON); however, few studies have addressed the CD4+T cells in ON related to sickle cell disease (SCD/ON). In addition, T cells producing multiple cytokines simultaneously are often present in the inflammatory milieu and may be implicated in the immune response observed in SCD/ON. In the present study, we aimed to characterize the functional status of CD4+T cells in SCD by simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The SCD HU− subgroup showed significantly higher mean leukocyte and neutrophil absolute count and mean CD4+ central memory and effector memory T-cell% count in comparison to controls, while CD3+ (PAN-T) cell% and CD4+ helper T-cell% were, on average, inferior when compared to controls. These results have a counterpart in the literature, where immunophenotyping of SCD patients off therapy was characterized by neutrophilic, lymphocytic and monocytic leukocytosis, along with a prevalence of memory on naïve T cells, interesting in a particular CD8+ subset in a context of T-cell compartment enlargement [ 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, other immunological features typical of SCD, such as expansions in CD8+ memory T-cell% and CD19+ B-cell% subsets and inversion of the CD4+/CD8+ ratio, were not observed in the SCD HU− subgroup, probably due to the small sample size [ 5 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The SCD HU− subgroup showed significantly higher mean leukocyte and neutrophil absolute count and mean CD4+ central memory and effector memory T-cell% count in comparison to controls, while CD3+ (PAN-T) cell% and CD4+ helper T-cell% were, on average, inferior when compared to controls. These results have a counterpart in the literature, where immunophenotyping of SCD patients off therapy was characterized by neutrophilic, lymphocytic and monocytic leukocytosis, along with a prevalence of memory on naïve T cells, interesting in a particular CD8+ subset in a context of T-cell compartment enlargement [ 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, other immunological features typical of SCD, such as expansions in CD8+ memory T-cell% and CD19+ B-cell% subsets and inversion of the CD4+/CD8+ ratio, were not observed in the SCD HU− subgroup, probably due to the small sample size [ 5 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 57%
“…We found that the mean CD4+ central memory T-cell% count was the only independent variable showing a positive correlation with crisis score in the multivariate analysis. This association probably reflects the role of persistent/chronic immune activation sustained by SCD-related inflammatory and infectious susceptibility in the impairment of T-cell regulation of B cells, favoring the differentiation process from naïve to memory T cells and eventually resulting in an immunosenescent-like phenotype [ 5 , 19 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophil represented the most plentiful class of cells in immune system, and they were migrated in lung epithelial cells infected by influenza viruses [22]. T lymphocyte subpopulation was generated during inflammatory reaction, and it was closely related to immune response [23]. T lymphocyte subpopulation was exhausted in lymphoid organs and peripheral blood infected with H1N1 to inhibit adaptive immune response [24].…”
Section: Discussionmentioning
confidence: 99%